Psychosocial and psychopathological predictors of HIV-risk injecting behavior among drug users in Portugal - Costa,Eleonora C. V. (2015)
Despite the introduction of needle and syringe exchange programs (NSPs), sharing of syringes and other materials remains common among injection drug users (IDUs) worldwide. For this reason, IDUs are at high-risk of HIV transmission. This paper studies the psychosocial and psychopathological determinants of sharing among IDUs. Understanding the relationship between psychological morbidity, HIV knowledge, HIV risk perception, and sharing behaviors is important to develop campaigns to curb sharing among IDUs. We recruited 120 male (76.7%) and female (23.3%) IDUs at a public outpatient treatment service in northern Portugal whose age average was 34 (sd=7.56). They were characterized for sociodemographic, clinical, and behavioral variables, as well as for knowledge on HIV transmission and prevention, HIV risk perception, and psychopathological symptoms. Almost all patients (95.8%) were tested for HIV and 31.7% were HIV positive. Half of them had a chronic disease (50.8%) and declared to engage in sharing (51.7%). Most had accurate knowledge of HIV transmission and prevention. A great majority deemed HIV risk to be high in their communities (80.8%) but deemed their personal risk to be zero or low (72.5%). Statistical analysis showed that sociodemographic variables (female sex, lower education, living alone) and psychopathological symptoms (obsession-compulsion and somatization) predict sharing. We conclude that the development and implementation of campaigns to reduce sharing among IDUs should focus more on women, IDUs living alone, as well as early assessment and intervention on psychopathological disorders.